A Methods engineering study on Dragon Textile Mills, Inc. - Derit, Lea Jacono; Martinez, Deanne Ambata; Pariño, Maria Karren Torrano; Patacsil, Gilberto Miguel Barot (College of Engineering, 2002)
DRAGON TEXTILE MILLS, INC. (DTMI) is one of the most advanced and modern textile mills in the country founded in 1988, having yarn as its major product. It is strategically located in Lalaan 2nd, Silang, Cavite because of its ideal weather condition, the proximity of the mill to Metro Manila and the availability of human resources in the locality. The DTMI's liason office is located in Binondo, Manila. DTMI now employs more than 100 people, inclusive of Officers and Manila staff. Using the tools and techniques in Methods Engineering like Streamline Diagnosis Diagram, the group identified several problems in the production area of DTMI. However, not all of them were verified. After thorough observation, the group came up with the core problem, which is the high risk of producing defective output in the production area particularly in the warehouse of Dragon Textile Mills, Inc. due to the overstocking of yarns produced. It has been found that the solution approach to the problems can be narrowed down. Instead of solving four root causes which are bending of pallet stacks due to lack of support, insufficient storage area, mishandling of finished products, and inappropriate doffing technique, the group decided to focus on the problems which can be solved quantitatively. These are bending of pallets due to lack of support and insufficient storage area. Thus, different alternatives for the solutions of the problems addressed were generated. For the insufficient storage area problem, four alternative courses of actions were developed. These are the installation of dividers, expansion of the storage area, expansion of storage area combined with usage of redesigned pallets, and expansion of storage area combined with the installation of hanging vertical supports. Rating them using several important criteria such as cost incurred, estimated useful life, ease of implementation, and less work disruption, expansion of the storage area was recommended. For the bending of pallet stack due to lack of support, the criteria mentioned above are also applied. Three alternative courses of actions were developed. These are the installation of hanging vertical steel supports attached to the ceiling extending down 2.5 meters toward the floor, installation of vertical steel supports attached to the floor extending four meters above it, and redesigning of pallets as requested from the supplier. The recommended solution was installation of hanging vertical supports, which received the highest over all score. Usage of redesigned pallets can also be considered as a solution since this alternative cannot be totally evaluated due to cost confidentiality. It must be noted that the above solutions are mutually exclusive. Therefore, if the company is considering solving both problems, both courses of actions must be done. As for the implementation, five stages of activities were established for the expansion of storage area. These are the manager's approval, current storage area evaluation, determination of the new storage area, deliberation and acquisition of materials to be used. For the implementation of the usage of redesigned pallets, five stages of activities were also established. These are the manager's approval, current pallet evaluation determination of the new pallets, deliberation and acquisition of the new pallets.